Analisis Perkembangan dan Determinasi Investasi Kabupaten dan Kota di Provinsi Riau - Ranti Darwin; Muhammad Hidayat; M Fikry Hadi (Universitas Dharma Andalas, 2019)
The purpose of this study was to determine the effect of government spending, investment lag, interest rates, inflation and economic growth on investment in Riau Province and Kotadi Regency. The data type of this research is panel data. In this study data was obtained from 12 districts / cities observed in a period of 6 years, 72 observations were obtained. In addition, secondary data was published by the Riau Province Central Bureau of Statistics (BPS). This study uses data analysis in the form of panel data regression analysis using EVIEWS 9.0 software. The results of this study indicate that government expenditure, investment lag, interest rates and inflation have a significant effect on investment in City District in Riau Province. While economic growth has a insignificant influence on investment in City District in Riau Province.